Dietary evidence from Central Asian Neanderthals: A combined isotope and plant microremains approach at Chagyrskaya Cave (Altai, Russia). Issue 156 (July 2021) - Salazar-García, Domingo C.; Power, Robert C.; Rudaya, Natalia; Kolobova, Ksenya; Markin, Sergey; Krivoshapkin, Andrey; Henry, Amanda G.; Richards, Michael P.; Viola, Bence
Abstract: Neanderthals are known primarily from their habitation of Western Eurasia, but they also populated large expanses of Northern Asia for thousands of years. Owing to a sparse archaeological record, relatively little is known about these eastern Neanderthal populations. Unlike in their western range, there are limited zooarchaeological and paleobotanical studies that inform us about the nature of their subsistence. Here, we perform a combined analysis of carbon and nitrogen stable isotopes on bone collagen and microbotanical remains in dental calculus to reconstruct the diet of eastern Neanderthals at Chagyrskaya Cave in the Altai Mountains of Southern Siberia, Russia. Stable isotopes identify one individual as possessing a high trophic level due to the hunting of large- and medium-sized ungulates, while the analysis of dental calculus also indicates the presence of plants in the diet of this individual and others from the site. These findings indicate eastern Neanderthals may have had broadly similar subsistence patterns to those elsewhere in their range.